Consumer preferences towards different rice varieties in polonnaruwa district - (:unkn) unknown (University of Jaffna, 2021)
This study evaluated the factors influencing the consumers’ preferences towards different rice varieties as well as identify the association between socio – demographic status and the preferences of rice varieties among the respondents in Polonnaruwa district. Data were collected from a random sample of 100 households who lives in rural and urban areas in Hingurakgoda DS division in the district during the period of May-June 2020. The collected data were analysed using frequency, chi – square test, multinomial probit model and its marginal effects. Frequency of consumer preferences on rice varieties revealed that, 48% of the households preferred Nadu followed by 40% and 12% of them chose samba and raw rice respectively. Further, 51% of the households eats rice at twice in a day whereas 42% and 7% of them eats rice thrice in a day and once in a day respectively. Results of chi- square test suggest that, association between residential places and preferences on rice varieties was higher than gender and opinion about the prices of rice. The results further indicated that about 58% of the households who lives in rural areas preferred Nadu while nearly 61% of the urban households preferred samba. However, nearly 14% and 8% of rural and urban households chose raw rice as their preferred rice respectively in the study. The multinomial probit model was used to assess the impact of socio – demographic, economic and consumption habits on household preferences towards rice varieties. Empirical results of the model indicated that among socio – demographic characters, gender, education and residential place whereas among economic and consumption habits, concern on price of rice and monthly income were significantly influenced on consumers’ preferences on rice varieties in the study. The findings of the study would help to the stakeholders in traditional rice industry to understand the underlining the patterns of consumers’ preferences towards different rice varieties in Polonnaruwa district.
Keywords: Consumers’ preferences on rice varieties; Consumption habits, socio – demographic status; Multinomial probit model